Assessment of bioclimatic conditions on Crete Island, Greece - Bleta, A.; Nastos, P. T.; Matzarakis, A. (Regional Environmental Change, 2014)
The objective of this study was to assess and analyze the human bioclimatic conditions of Crete Island, by applying two human thermal indices: physiological equivalent temperature (PET), derived from the Munich Energy-balance Model for Individuals human energy balance model, and Universal Thermal Climate Index (UTCI), based on the Fiala multi-node model of human thermoregulation. Human bioclimatic studies provide a framework for considering the effects of climatic conditions on human beings and highlighting the social/economic factors that mitigate or amplify the consequences of environmental changes. In order to estimate the thermal effect of the environment on the human body, it has been considered that the total effects of all thermal components, not only of individual parameters, should be taken into account. The climatic data (air temperature, relative humidity, cloudiness, wind speed) used in this study were acquired from the archives of the Hellenic National Meteorological Service, regarding ten meteorological stations in Crete Island. These data, covering the 30-year period 1975–2004, were used for the calculation of PET and UTCI in order to assess thermo-physiological stress levels. The findings of this analysis, such as bioclimatic diagrams, temporal and spatial distributions of PET and UTCI as well as trends and variability, will help stake holders to understand and interpret the island’s current bioclimate, in order to make any necessary adaptations and become more resilient to the foreseen climate change. © 2013, Springer-Verlag Berlin Heidelberg.
Keywords: Bioclimatic conditions; Crete Island; PET; UTCI